Profiling the Two Most Populous Generations of the PIIGS countries in the Workplace based in Online Consumption of Cultural Contents - Trindade, G.; Laureano, Raul M. S. (2019 14th Iberian Conference on Information Systems and Technologies (CISTI), 2019)
The technological advances and the massive use of the Internet have led to the emergence of new business models based on the access online. One of the industries that most visibly had to adapt to the new reality was the production and dissemination of cultural contents, preparing for a consumer that is already native or casual digital. However, the new business model, especially, the one which implies access paid to cultural content, namely music, movies, TV series, images and news, does not still show a great success. In order to understand how the consumers of the generations X and Y (Millennials), from countries with unfavorable economic conditions, known as PIIGS, have adhered to the reality of online consumption of cultural content. The results from the Flash Eurobarometer 437: "Internet users' preferences for online accessing content" show the existence of three groups of consumers, and only one of them has a propensity to access paid content. Thus, by knowing the profiles of these three groups of consumers, it is possible to direct marketing campaigns tailored to each of them and to evaluate possible ways to convert consumers that only use of free services into consumers of paid services.